Answer:
B is correct.
Step-by-step explanation:
Compound Interest Formula:
![V(t)=P(1+\frac{r}{n})^{nt}](https://tex.z-dn.net/?f=V%28t%29%3DP%281%2B%5Cfrac%7Br%7D%7Bn%7D%29%5E%7Bnt%7D)
Tasha invests in two ways
Case 1:
- Principal P=$5,000
- Rate of Interest r=0.06
- Time t=t
- n=1
![V(t)=5000(1+0.06)^t](https://tex.z-dn.net/?f=V%28t%29%3D5000%281%2B0.06%29%5Et)
![V(t)=5000(1.06)^t](https://tex.z-dn.net/?f=V%28t%29%3D5000%281.06%29%5Et)
Case 2:
- Principal P=$5,000
- Rate of Interest r=0.08
- Time t=1
- n=1
![V(t)=5000(1+0.08)^t](https://tex.z-dn.net/?f=V%28t%29%3D5000%281%2B0.08%29%5Et)
![V(t)=5000(1.08)^t](https://tex.z-dn.net/?f=V%28t%29%3D5000%281.08%29%5Et)
Total amount yield by Tasha = ![5000[(1.06)^t+(1.08)^t]](https://tex.z-dn.net/?f=5000%5B%281.06%29%5Et%2B%281.08%29%5Et%5D)
Thomas Investment
- Principal P=$10,000
- Rate r= 0.07
- t=t
- n=1
Total amount yield by Thomas = ![10000(1.07)^t](https://tex.z-dn.net/?f=10000%281.07%29%5Et)
Now we make table for Tasha and Thomas different value of t
t Tasha Thomas
1 $10,700 $10,700
2 $11,450 $11,449
3 $12,254 $12,250
4 $13,115 $13,108
In table we can see Tasha investment will yield more from Thomas.
Thus, Tasha’s investment will yield more over many years because the amount invested at 8% causes the overall total to increase faster.
45 = 3x3x5
Or you could simplify it to 3^2x5
Answer:
Option D. 11√6/2
Step-by-step explanation:
We'll begin by calculating the side opposite to angle 60°.
This is illustrated below:
Angle θ = 60°
Opposite =?
Hypothenus = 11
Using the sine ratio, we can obtain the side opposite to angle 60° as follow:
Sine θ = Opposite/Hypothenus
Sine 60 = Opposite /11
Cross multiply
Opposite = 11 × Sine 60
Sine 60 = √3/2
Opposite = 11 × √3/2
Opposite = 11√3/2
Finally, we shall determine the value of x as follow:
Angle θ = 45°
Opposite = 11√3/2
Hypothenus = x
Using the sine ratio, we can obtain the value of x as shown below:
Sine θ = Opposite/Hypothenus
Sine 45° = 11√3/2 /x
Cross multiply
x × Sine 45° = 11√3/2
Sine 45° = 1/√2
x × 1/√2 = 11√3/2
x/√2 = 11√3/2
Multiply through by √2
x = √2 × 11√3/2
x = 11√6/2
Answer:
52 ft^2
Step-by-step explanation:
To find the area you just multiply 13 feet (length) by 4 feet (width). This gives you 52 feet squared because we are dealing with area and square feet.